Perlindungan Hukum Terhadap Tenaga Kerja Anak Ditinjau Dari Undang-Undang No. 13 Tahun 2004 Tentang Ketenagakerjaan - Nabiella Putri Nastiti; Christina Febriani Silalahi; Adisty Maharani; Anzira Sania Deshiva; Mita Riza Rahmanda; Goldman Mediyana; Reza Dio Wijatmika; Alief Anugrah; Mustika Mega Wijaya (Jurnal Hukum dan Sosial Politik, 2023)
This research aims to examine the legal protection provided by law to a child who becomes a worker in protecting and maintaining the legal rights and growth and development rights of a child. As well as providing knowledge for a child who will become a worker and for a business owner in employing a child into the workforce so that both parties understand their respective rights and obligations. This research was conducted in order to contribute to the legal protection of a child so that the growth and development of children can be guaranteed and protected properly and is intended to be useful for readers and add insight that is so important in applying special treatment for a child who becomes a worker.